De la difficulté de fabriquer des objets-frontières - Céline Verchère; Emmanuel Anjembe (Revue d'anthropologie des connaissances)
Faced with the “requirement to innovate” design projects for technological innovations have increasingly relied on the social sciences in recent times. These approaches often necessitate the material actualisation of knowledge production in different forms (films, screenplays, etc). This article focuses on the study of such a project, wherein the boundary‑object concept, introduced by the social researchers, is operationalised in order to facilitate the depiction of objects created in an interdisciplinary context. By returning to the objects production, we will demonstrate how the project’s identity is redefined following the introduction of this notion, as well as the difficulties faced in the process of making such objects: in reality, the objects assume diverse forms and follow complex trajectories. Furthermore, this analysis clarifies the project’s dynamics and the project’s outcome shifts in perception, by highlighting the tensions related to the heterogeneous languages and to the standards’ weakness.